Dispositif d’accompagnement en réalité virtuelle pour adultes autistes dyscommunicants - Cécile Lacôte-Coquereau (Recherches en Éducation)
Despite institutional injunctions, people with disabilities remain little involved in inclusive processes at the heart of the city. In this sense, how can we facilitate the evolution of the living context of young adults with autism residing in institutions towards an inclusive shared habitat in an urban environment; a societal and ethical issue of full citizen participation? In collaborative research, we present here a specific support system, via innovative virtual reality systems, aiming at the development of interactions, autonomy and the power to act of dyscommunicating autistic people. Indeed, if the literature shows that digital tools can promote the cognitive availability and stimulate the engagement of autistic individuals, how can we allow their effective participation and support their learning via virtual reality capsules? The results, in anthropological evidence, fall within the framework of activity theory.